Ecological effects of forestry practices in long-established woodland and their implications for nature conservation - Mitchell, P; Kirby, K (Oxford Forestry Institute, University of Oxford, 1989)
Concern has been expressed about the damaging effects of modern forestry practices in Great Britain on the nature conservation values of long-established woodland. It is less often appreciated how far traditional forestry practices such as coppicing themselves altered the structure and composition of the original forests. This review compares the effects of modern and traditional forest practices on the soils, flora and fauna of British woods. Effects are allocated {as far as possible} between those due to a change of tree species, those caused by changes in stand or woodland structure and those due to other changes which take place under modern forestry management such as fertilization, or the application of pesticides. A complex pattern emerges where no single forestry system (traditional or modern) is likely to favour all groups of organisms, so that it is essential for nature conservation objectives to be defined as precisely as possible for any given wood. This is particularly true in small woods (less than 10 hectares) where there is little opportunity to vary the treatments applied to different areas. In general the review has confirmed that nature conservation interests are best served by systems which make use of trees and shrubs native to the site; use relatively small coupes, but contain also some larger open areas (either permanent glades or temporary clearings); keep some over-mature trees and dead wood; and minimize soil disturbance, fertilization, pesticide use and drainage. These tend to be more commonly associated with traditional systems of management such as coppice or coppice with standards than with modern forestry practice. By contrast the practices that have been favoured in commercial forestry during the last forty years do tend to reduce the overall species or habitat diversity: the use of heavy shade-casting trees such as spruce, relatively large coupes (over 5 ha), few if any trees retained beyond maturity , a preponderance of stands all of a similar age, and intensive ground preparation techniques. There is however some scope for offsetting the more damaging effects of modern forestry on nature conservation interests, for example by heavier thinning where a heavy shade-caster is used. Equally, traditional practices can be improved upon, by leaving some areas undisturbed to grow on to high forest. Hence it is worth analysing, for any site what elements of modern forestry are the most serious (in nature conservation terms), because it may be possible to change them without necessarily abandoning commercial management altogether. There will s till be economic penalties (revenue forgone or cost increases) from so doing, but these are inevitable if nature conservation is genuinely to be accepted as an objective of woodland management. There is a need for more monitoring of managed stands to improve our understanding of the effects of modern forestry, which should be combined with short-term experiments on some of the crucial issues and practices.